2017
DOI: 10.1002/2016jd026183
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characteristics of Convective Clouds over the Western Ghats Derived from Weather Radar Observations

Abstract: X‐band radar observations at Mandhardev (18.04°N, 73.85°E) are used to investigate statistics of convective clouds over the Western Ghats during monsoon season (June–September 2014). Convective storms (cells) are identified using an objective‐tracking method to examine their spatiotemporal variability, thus quantifying the time‐continuous aspects of convective cloud population over the region for the first time. An increased frequency of storm location and initiation along the windward mountains compared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 66 publications
(155 reference statements)
6
43
0
Order By: Relevance
“…Kumar and Bhat (2017) also showed that the TRMM convective/stratiform identification algorithm classified rainfall offshore from the Indian west coast as convective more frequently than in other similar regions. Utsav et al (2017) used ground-based weather radar observations at the northern end of the Western Ghats to show that this is most frequently congestus-type convection. While most rainfall upstream of the Western Ghats comes from convective clouds with tops below about 6 km, the most intense rainfall comes from organized large-scale features such as the northward propagation of the tropical convergence zone (Francis and Gadgil, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Bhat (2017) also showed that the TRMM convective/stratiform identification algorithm classified rainfall offshore from the Indian west coast as convective more frequently than in other similar regions. Utsav et al (2017) used ground-based weather radar observations at the northern end of the Western Ghats to show that this is most frequently congestus-type convection. While most rainfall upstream of the Western Ghats comes from convective clouds with tops below about 6 km, the most intense rainfall comes from organized large-scale features such as the northward propagation of the tropical convergence zone (Francis and Gadgil, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been few ground‐based studies on orographic convection documenting the radar divergence profiles (Deshpande et al, ) and drop size distributions (Das et al, ; Konwar et al, ). Utsav et al () derived the statistical characteristics of convective clouds over the WG during monsoon using the X‐band radar observations. Although these studies describe the orographic rainfall characteristics over this region, the vertical structure of convective clouds, especially during the monsoon intraseasonal phases, remains to be documented and is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Konwar et al (2006) and Rao et al (2009) showed that stratiform precipitation dominates over Gadanki. However, shallow convection occurs frequently over WGs (Utsav et al, 2017). This indicates that the rain microphysical processes are different over WGs compared to other regions.…”
Section: Average Raindrop Spectramentioning
confidence: 99%
“…It receives a large amount of rainfall (~6000mm) during the Indian Summer Monsoon (ISM; , and references therein). The monsoon rainfall in this region is contributed by both shallow clouds on the windward side (Kumar et al, 2013;Utsav et al, 2017Utsav et al, , 2019 and deep convection in the leeward side (Utsav et al, 2017(Utsav et al, , 2019Maheskumar et al, 2014). In addition, thunderstorms also occur over WGs; however, they are very few during the monsoon period.…”
Section: Introductionmentioning
confidence: 98%